Brief Report: Ultraviolet Radiation Exposure Is Associated With Clinical and Autoantibody Phenotypes in Juvenile Myositis1. Issue 7 (2nd July 2013) - Shah, Mona; Targoff, Ira N.; Rice, Madeline M.; Miller, Frederick W.; Rider, Lisa G.; ,
Abstract : Objective: Genetic and environmental factors may contribute to the etiology of the juvenile idiopathic inflammatory myopathies (IIMs), which are systemic autoimmune diseases that are characterized by muscle and skin inflammation. We undertook this study to investigate the association between ultraviolet radiation (UVR) exposure and the clinical and autoantibody expression of juvenile IIM. Methods: The relationship between UVR exposure in the month before symptom onset and the prevalence of juvenile dermatomyositis (DM), compared to juvenile polymyositis (PM), was assessed in 298 juvenile IIM patients. Among the patients with juvenile DM, the association between UVR exposure and presence of myositis autoantibodies was assessed. Regression models were stratified by sex and race. The association between the regional UV index in US geoclimatic zones and the clinical and autoantibody subgroups was examined by weighted least squares regression analysis. Results: Among girls in this population, the odds of having juvenile DM, compared to juvenile PM, increased per unit increase in the patients' highest UV index in the month before symptom onset (odds ratio [OR] 1.18, 95% confidence interval 1.00–1.40). Moreover, both the mean and highest UV indices were associated with increasing odds of having anti‐p155/140 autoantibodies, with the strongest odds in white males (ORs of 1.30 and 1.23, respectively). No association was observed between the UV index and presence of anti‐MJ autoantibodies or lack of any myositis autoantibodies. Across all 9 US geoclimatic regions, the mean UV index was associated with increasing odds of having juvenile DM and anti‐p155/140 autoantibodies, but decreasing odds of having anti‐MJ autoantibodies. Conclusion: Short‐term UVR exposure prior to illness onset may have a role in the clinical and serologic expression of juvenile myositis. Further research examining the mechanisms of action of UVR in the pathogenesis of juvenile IIM is suggested from these findings.